Implementasi Pembelajaran Model Blended Learning di SMPN 3 Langkap Lancar Pangandaran Pada Pandemi Covid-19 - Titaniar Jaga Paramudita; Sri Yulianti; Erlina Terawati; Unik Hanifah Salsabila (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to describe the implementation of the VIII A blended learning model at SMP N 3 Langkap Lancar Pangandaran during the Covid-19 pandemic. This research is a quantitative research through interview technique. The resource persons are teachers of Islamic Religious Education and Good Character. In addition to using interviews, researchers collect information through literature study. The blended learning method is a learning method that mixes face-to-face learning with online or online learning. The results of the study revealed that from the number of class VIII A students, namely 28 students, the blended learning learning process was carried out since the government gave permission to apply the model. The learning process of the blended learning model is still being implemented until now. The initial preparation for learning is by adjusting the schedule of students who take online learning with students who take face-to-face learning. When the initial application of online learning was implemented in schools, the student's academic achievement value decreased. After students and all aspects of education have successfully adapted to the situation, the average value of students tends to be more stable and even has increased, supported by the use of more practical educational technology.